Decoding Patient Satisfaction: Examining the Hospital Facilities, Staff Behavior, and Accessibility (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
Background: This study explores patients' perceptions of hospital facilities, staff behavior, and accessibility, with the aim to assess their relationships and impacts on overall patient satisfaction. As healthcare quality and patient experience become critical components of service delivery, this research investigates how different hospital factors contribute to patient satisfaction levels.Research Methods: Adopting a descriptive and causal-comparative research design, this study utilized a deductive approach to test hypotheses based on literature. Data were collected through structured surveys with 200 patients, using a four-point Likert scale to measure responses.Results: The study found that hospital staff behavior significantly influenced patient satisfaction, with 96% of participants rating the staff as friendly, respectful, and prompt in attending to their needs. Cleanliness and maintenance of hospital facilities were also positively perceived, with 52% of respondents highlighting that facilities were well-maintained. Furthermore, accessibility to medical services, including appointment scheduling and timely care, had a positive correlation with overall satisfaction, as 79.5% of respondents found it easy to schedule appointments and receive care. A small minority reported dissatisfaction with either facilities or service responsiveness, signaling areas for potential improvement.Conclusion: The research demonstrates that patient satisfaction is strongly influenced by positive perceptions of staff behavior, hospital facilities, and service accessibility. Ensuring consistent staff professionalism, maintaining hospital cleanliness, and enhancing accessibility can significantly improve overall patient satisfaction. These findings suggest that hospitals aiming to enhance patient experiences should prioritize these factors, particularly focusing on staff training, facility management, and streamlining patient access to care.